Freedom of Expression in Pakistan and Malaysia: A Comparative Legal Analysis - Nisar Mohammad Ahmad; Kashif Mahmood Saqib (Indus Journal of Social Sciences, 2025)
Pakistan and Malaysia have distinct legal and social settings, which have an impact on the ideas and experiences around freedom of expression in both nations. The Pakistani Constitution guarantees the right to freedom of expression, notwithstanding heavy limitations, particularly with regard to national security concerns. Similarly, the Federal Constitution of Malaysia though guarantees freedom of expression, laws related to defamation and sedition are used to impose restrictions. In Pakistan, courts have struggled to find equilibrium between freedom of expression and the state's obligation to uphold morality and public order, frequently leading to controversial decisions. The Malaysian judiciary has also encountered difficulties in striking a balance between the freedom of expression and regulations intended to maintain ethnic and racial peace, which frequently results in the silence of dissenting opinions. Social and cultural aspects are major determinants of this valuable right in both nations. Historical circumstances influence how freedom of expression is understood and applied, such as Malaysia's multicultural society and Pakistan's colonial heritage. The importance of digital platforms and social media, in addition to other recent developments and trends, significantly muddies the landscape of free speech in these nations. In order to shed light on the opportunities and obstacles for advancing this fundamental right in various socio-political situations, this article aims to identify parallels, contrasts, and growing patterns on how Pakistan and Malaysia negotiate the complicated terrain of freedom of expression. The research continues by looking at court rulings and significant cases that have influenced each nation's jurisprudence. The study in this article is based on a library-based method where several books, articles, court cases, internet sources etc are analysed to obtain the data. This research found that much work was yet to be done to improve the right to freedom of expression in Pakistan and Malaysia.